Rates of Upper Facet Joint Violation in Minimally Invasive Percutaneous and Open Instrumentation: A Comparative Cohort Study of Different Insertion Techniques - Archavlis, Eleftherios; Amr, Nimer; Kantelhardt, Sven Rainer; Giese, Alf (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Minimally invasive pedicle screw placement may have a higher incidence of violation of the superior cephalad unfused facet joint.Study Aims We investigated the incidence and risk factors of upper facet joint violation in percutaneous robot-assisted instrumentation versus percutaneous fluoroscopy-guided and open transpedicular instrumentation.Methods A retrospective study including all consecutive patients who underwent lumbar instrumentation, fusion, and decompression for spondylolisthetic stenosis and degenerative disk disease was conducted between January 2012 and January 2016. All operations were performed by the same surgeon; the patients were divided into three groups according to the method of instrumentation. Group 1 involved the robot-assisted instrumentation in 58 patients, group 2 consisted of 64 patients treated with a percutaneous transpedicular instrumentation using fluoroscopic guidance, and 72 patients in group 3 received an open midline approach for pedicle screw insertion.Results Superior segment facet joint violation occurred in 2 patients in the robot-assisted group 1 (7%), in 22 of the percutaneous fluoroscopy-guided group 2 (34%), and in 6 cases of the open group (8%). The incidence of facet joint violation was present in 5% (3) of the screws in group 1, 22% (28) of the screws in group 2, and 3% (4) of the screws in group 3.Conclusion Meticulous surgical planning of the appropriate entry site (Weinstein's method), trajectory planning, and proper robot-assisted instrumentation of pedicle screws reduced the risk of superior segment facet joint violation.
Keywords: upper facet joint; robot-assisted; percutaneous instrumentation; minimally invasive